Model organisms in inflammation and cancer - Yiorgos Apidianakis (Frontiers Research Topics, 2014)
A link between inflammation and cancer was initially made by Rudolf Virchow back in the 19th century. Nowadays many cancers are considered dependent on inflammatory responses to microbial and damaged-self stimuli and both arms of immunity, innate and adaptive, are playing a role in promoting cancer. Moreover, besides environmental factors, opportunistic pathogens contribute to inflammation and cancer. Nevertheless, microbial influence on chronic disease is sometimes difficult to discern, especially in the context of polymicrobial communities, such as those found in the digestive tract. In this light, model organisms provide important insights into immune and growth signals that promote cancer, and suggest therapies that will selectively target potentially harmful microbes or modulate host responses. A number of review and opinion articles in this series address novel aspects and paradigms of the interactions between the microbiota and the host in relation to inflammation and cancer.